Evolution and expression of genes encoding TCP transcription factors in Solanum tuberosum reveal the involvement of StTCP23 in plant defence - Sarina Bao; Zhenxin Zhang; Qun Lian; Qinghua Sun; Ruofang Zhang (BMC Genetics, 2019)
Abstract Background The plant-specific Teosinte branched1/Cycloidea/Proliferating cell factor (TCP) family of transcription factors is involved in the regulation of cell growth and proliferation, performing diverse functions in plant growth and development. In addition, TCP transcription factors have recently been shown to be targets of pathogenic effectors and are likely to play a vital role in plant immunity. No comprehensive analysis of the TCP family members in potato (Solanum tuberosum L.) has been undertaken, however, and whether their functions are conserved in potato remains unknown. Results To assess TCP gene evolution in potato, we identified TCP-like genes in several publicly available databases. A total of 23 non-redundant TCP transcription factor-encoding genes were identified in the potato genome and subsequently subjected to a systematic analysis that included determination of their phylogenetic relationships, gene structures and expression profiles in different potato tissues under basal conditions and after hormone treatments. These assays also confirmed the function of the class I TCP StTCP23 in the regulation of plant growth and defence. Conclusions This is the first genome-wide study including a systematic analysis of the StTCP gene family in potato. Identification of the possible functions of StTCPs in potato growth and defence provides valuable information for our understanding of the classification and functions of the TCP genes in potato.